FUNCTIONAL ESSENCE OF DIPLOMATIC AND CONSULAR IMMUNITIES: THEIR ROLE IN ENSURING THE STABILITY OF INTERNATIONAL RELATIONS (Multidisciplinary Journal of Science and Technology, 2026)
This scientific article analyzes the functional nature of diplomatic and consular immunities in international law, their role as a legal guarantee that serves the effective performance of the tasks of interstate communication, representation, negotiation, information exchange and protection of the interests of citizens, not as a personal privilege. The study examines the theoretical and legal foundations of immunities, the differences between diplomatic and consular immunities, their impact on the stability of international relations, and the mechanisms of legal balance against abuse, based on the 1961 Vienna Convention on Diplomatic Relations, the 1963 Vienna Convention on Consular Relations, international judicial practice and doctrinal sources.